The Red Badge of Courage: An Episode of the American Civil War - Crane, Stephen, 1871-1900 (Salt Lake City, UT : Project Gutenberg, 1993)
"The Red Badge of Courage: An Episode of the American Civil War" by Stephen Crane is a war novel published in 1895. The story follows Henry Fleming, a young Union Army private who flees from battle during the American Civil War. Overwhelmed by shame and cowardice, he desperately longs for a wound$1 (Ba "red badge of courage"$1 (Bto redeem himself. When his regiment faces combat again, Henry must confront his fears. Known for its psychological realism and vivid battle sequences, the novel explores themes of maturation, heroism, and the true nature of courage. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Red_Badge_of_Courage
Release date is 1993-07-01
Arthur Smith
Keywords: Historical fiction; War stories; United States -- History -- Civil War, 1861-1865 -- Fiction; Virginia -- History -- Civil War, 1861-1865 -- Fiction; Chancellorsville, Battle of, Chancellorsville, Va., 1863 -- Fiction